2006
DOI: 10.1093/jmedent/43.2.344
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering of West Nile Virus in Southern California

Abstract: West Nile virus (family Flaviviridae, genus Flavivirus, WNV) invaded southern California during 2003, successfully overwintered, amplified to epidemic levels, and then dispersed to every county in the state. Although surveillance programs successfully tracked and measured these events, mechanisms that allowed the efficient overwintering and subsequent amplification of WNV have not been elucidated. Our current research provided evidence for three mechanisms whereby WNV may have persisted in southern California … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
101
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 57 publications
12
101
0
Order By: Relevance
“…According to the PDSI values as shown in Based on the results of environmental factor analysis, the positive role of temperature detected in the environmental factor analysis is consistent with the finding reported by Reisen et al [41,42]. Temperature must be above the minimum temperature (14.3°C) required for virus replication in mosquitoes for WNV to be disseminated throughout the year, especially in the cold months [42].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…According to the PDSI values as shown in Based on the results of environmental factor analysis, the positive role of temperature detected in the environmental factor analysis is consistent with the finding reported by Reisen et al [41,42]. Temperature must be above the minimum temperature (14.3°C) required for virus replication in mosquitoes for WNV to be disseminated throughout the year, especially in the cold months [42].…”
Section: Discussionsupporting
confidence: 87%
“…Temperature must be above the minimum temperature (14.3°C) required for virus replication in mosquitoes for WNV to be disseminated throughout the year, especially in the cold months [42]. A temperature study in southern California showed that mean temperatures in Coachella Valley in Riverside County and the hilly parts of Los Angeles County were mainly above the minimum in the coldest months of years 2003-2005, while temperatures in Long Beach, Los Angeles and Shafter, Kern County floated around the minimum in the same period of time, and the differences increase during summer [41]. The results also show that areas with lower elevations tended to be more susceptible to WNV invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three mechanisms have been proposed for the overwintering of WNV: (1) continued enzootic transmission, (2) chronic infections in living birds, and (3) vertical transmission of virus (Reisen et al 2006). Of these, within-winter seroconversion of an individual bird is consistent with the first two mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…We report on the results of epitope-blocking ELISAs detecting WNV antibodies in overwintering migrant and permanent resident bird species in south-central Kansas during the winters of 2003-04 through 2005-06. Serial sampling was used to detect within-winter seroconversion of overwintering passerines, that could provide preliminary support for a role of enzootic transmission and/or chronic infection as overwintering mechanisms (Reisen et al 2006). In addition, many avian species were captured and assayed in the first general survey of seropositivity in this geographic region.…”
Section: Introductionmentioning
confidence: 99%